Online Halaqah:The Adoption of Digital Media Technology for Religious Learning in Pesantren As‘adiyah, Wajo, South Sulawesi - Halim, Wahyuddin; Akbar , Akbar; Tahir, Tarmizi (Al-Ulum, 2024)
This study examines the use of digital media by Pesantren As'adiyah in South Sulawesi through its online halaqah program, initiated during the Covid-19 pandemic. Employing a qualitative approach, data were gathered through both online and offline fieldworkin Wajo and other regions in Indonesia and analyzed using a thematic approach. The findings reveal that the primary objective of the online halaqah was to accommodate students returning to their hometowns during the pandemic. Over time, however, it expanded to include a broader audience. Pesantren adapted its methods and duration to align with the online format, which has recently evolved into a parallel coverage of offline halaqah held at the pesantren. In conclusion, despite its limited impact, the online halaqah has contributed to maintaining religious education, embraced digital technology, and extended its benefits to a wider community